Analysis of The Influence of Technology, Latest Working Equipment Usage, and Industrial Relations Strategies Towards Business Sustainability - Kurnia Harahap, Muhammad Ade; Rohman, Saeful; Assery, Syeh; Widarman, Agung; Chatra, Afdhal (Jurnal Informasi dan Teknologi, 2024)
This research aims to contribute to modern business, new work systems, and industrial relations. This research is a longitudinal study involving manufacturing companies. Researchers collected data at two different periods. Researchers surveyed by sending a questionnaire to the company's human resources managers. Research findings show a reasonably strong relationship between implementing new work practices and better company results. However, according to the dominant theory, this result does not always occur in every case. These results indicate a greater focus on small businesses, which play a significant role in the fabric industry. The third result shows the durability or sustainability of individual practices. These new practices have proven effective in improving company performance, which may be why groups are more confident implementing them. Discriminant analysis reveals that firms' structural and market characteristics account for most of the variability in their orientation toward organizational innovation. The intensity of relationships with other companies positively correlates with using new work practices, mainly if the company operates internationally. The competition level in the company's market is also related to the use of new work practices and intense, innovative activities, especially those related to technology and the coordination of activities within the organization, such as information technology.